Hemisphere dominance in cochlear implanted children - Runjić, Nađa (Array, 2003)
Cochlear implant is technologically most sophisticated hearing aid that provides optimal development of hearing and speech. If peripheral input is enabled the hearing is not yet achieved, because the central mechanisms have been inactive and have to "learn" how to transmit the acoustic information, how to clean and structure the signal. In most humans, the left cerebral hemisphere is dominant for language processing. The aim of the paper was to investigate if there was a difference in hearing and speech in children with cochlear implants depending on the side of implantation, and to assess the impact of early implantation on hemispheric dominance (the effect of peripheral function on the central one). Twenty prelingually deaf children with cochlear implants, aged between 3 and 11 years were tested. The children were rehabilitated according to Guberina's verbotonal method at the SUVAG Polyclinic, Zagreb. Pure tone audiometry, auditory brainstem responses, middle latency responses, speech audiometry, verbotonal audiometry and psychologic evaluation were performed. The results were compared according to lateralization of function, speech and hearing evaluation. After one year of cochlear implantation and rehabilitation, the subjects showed significant improvement in hearing level, speech perception and production. Children with cochlear implant in the dominant ear had better hearing than the control group. The first results indicate a significant role of hemisphere dominance in hearing achievement in cochlear-implanted children. The peripheral hearing function influences the central listening abilities and lateralization in auditory processing.